(3eNJUQ cJGH GddhGeY aj GdLeY ef GdUMGM hGdLhGeYs - (3eLghds; (3CHh GdYHGS CMeO Hf KGHJ GdCUHgGfj,J (B520 (3g` s
(3ChdgG (B:s
(3jHJOF HHbjI eSfO YHO Gddg Hf YHGS QVi Gddg Yfg Hbhdg Cf QShd Gddg Udi Gddg Ydjg hSde fgi Cf JJRhL GdeQCI Ydi YeJgG Ch Ydi NGdJgG s
(3BNQgG (B:s
(3jfJgi HBNQ eSfO CHj gQjQI YHO GdQMef Hf UNQ QVi Gddg Yfg s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3eUOQ GbJfGA GdCUd (B:s
(3ajV Gddg (B(502) s
Keywords: (3GdMOjK h GdeUWdMs